Implementasi Kurikulum Merdeka Dalam Proses Pembelajaran (Surveri di SMK Negeri 33 Jakarta) - Sabrina Rosadi; Kunaenih; Nadiah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
The background of this research is to determine the implementation of the independent curriculum in the learning process, as well as the obstacles faced, especially in the implementation of PKL. The school and Islamic Religious Education teachers are given the responsibility to ensure that students continue to carry out summative learning in the midst of the PKL implementation. The researcher has made a simple observation that at SMK Negeri 33 Jakarta there are still students who have difficulty in learning Islamic Religion during PKL. Therefore, the reason the researcher undertook this research was to find out how Islamic Religious Education teachers overcome problems in this regard, what obstacles and solutions the school and Islamic Religious Education teachers provide. The aim is to ensure that students continue to receive maximum Islamic Religious Education learning during PKL. The research method used in this study is descriptive qualitative. The research data sources are Islamic Religious Education teachers, the Deputy Curriculum of SMK Negeri 33 Jakarta, peer teachers, and students. The data analysis techniques used were data presentation and conclusion drawing. This study used a validity test using research data using source triangulation. Based on the results of the study, it shows that teachers and the school strive to ensure that the implementation of PKL does not interfere too much with Islamic Religious Education learning. With this, teachers arrange an Islamic Religious learning schedule by adjusting the work schedule during PKL with the Islamic Religious Education learning schedule, because it will not be the same as in-class learning, learning is done online and uses platforms such as zoom, PowerPoint and others. The obstacles experienced by Islamic Religious Education teachers and students, namely Islamic Religious Education learning. There was a decrease in grades after carrying out PKL, and due to being far from teacher supervision, there were several reported problems such as not praying obligatory. Therefore, the solution is, teachers must be able to get good time, as well as interesting learning. And provide input between teachers and students to improve grades. Keywords: Implementation of the Independent Curriculum, Islamic Religious Education, Work Experience